(untitled) (Al-Academy, 2024)
This research knocks on one of ancient Greek sculpture art doors was not opened very often. it’s short but important interim period in its development process, between what was called the Archaic and the Classical period, approximately 30 years in which the sculptor departed from a style that had been prevalent for many decades, relying on repetition and reduction to a more style. Freedom and experimentation. The first Chapter provided a general introduction to this phase: naming, its historical and geographical framework, Circumstances that led to its emergence, followed by tracing the style of its sculptures and monitoring, their techniques and materials, then mentioning the most important sculptors who were attributed to this phase. In the second Chapter the research sample was selected and analyzed to Extract a results and conclusions which included: the Severe sculpture tends toward simplification in treating the form and seeks to break the rigid symmetry and leave the Archaic smile. The Bronze was adopted as the first material instead of stone, and more